Sensitive non-radioactive dot-blot hybridization using DNA probes labelled with chelate group substituted psoralen and quantitative detection by europium ion fluorescence. - Oser, A (1988)
A new labelling method for cloned DNA probes used in hybridization assays is described. The DNA insert of recombinant plasmid DNA was made partially single-stranded for the labelling reaction by a restriction enzyme digest, followed by a controlled exonuclease III incubation. A thiol-containing psoralen derivative was covalently bound through irradiation with UV-light to the remaining double-stranded region of the plasmid DNA. The psoralen-SH groups were labelled with a large number of metal chelators (diethylentriamine pentaacetic acid, DTPA) using poly-L-lysine as a macromolecular carrier. The main advantage of the labelling procedure is that a high degree of labelling is achieved without modification of the single-stranded DNA hybridizing sequences. The specific hybrids were labelled after filter hybridization with europium ions through the chelating groups of DTPA. The europium ions were quantitatively detected by time-resolved fluorometry. The sensitivity of the assay for target DNA detection was in the low picogram range, comparable to radioactively labelled DNA probes.